2019
DOI: 10.18203/2394-6040.ijcmph20192286
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the salivary glucose as a non-invasive test for diabetic patients

Abstract: Background: Over the recent year there has been a startling rise in the number of people suffering from diabetes mellitus. Estimation of blood glucose levels has been an essential laboratory investigation for screening and monitoring of diabetes. Saliva is one of the secretions in human body whose collection is easy and non-invasive. Salivary glucose hence could serve as an easy and non-invasive tool.Methods: Institutional review committee of NHRC gave us permission to carry out this study. 105 subjects with T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Diabetes mellitus is a complex multi-system endocrine disorder which can lead to potentially devastating complication that can affect all age group worldwide. [16] Electrolyte imbalance occurs in type 2 diabetes results from hyperglycemia. Several previous studies have shown disturbed electrolyte distribution in serum of type 2 diabetic patients.…”
Section: Discussionmentioning
confidence: 99%
“…Diabetes mellitus is a complex multi-system endocrine disorder which can lead to potentially devastating complication that can affect all age group worldwide. [16] Electrolyte imbalance occurs in type 2 diabetes results from hyperglycemia. Several previous studies have shown disturbed electrolyte distribution in serum of type 2 diabetic patients.…”
Section: Discussionmentioning
confidence: 99%